Bordelek hernia causing right ureteric obstruction with pyelonephritis. Issue 5 (2016) - Kanno, Masatomo; Oshita, Fumihiro; Yoriko, Kuboi; Ueta, Shinsuke; Kawata, Natsuki; Kurakami, Yuichi; Matsubayashi, Mao; Iwabuchi, Keisuke; Fumihiro, Yohsuke; Ohta, Mitsuyasu; Watanabe, Takeshi; Yoshie, Kohichiro
No abstract available